(untitled) (Journal of the College of Basic Education, 2022)
Great efforts are being made by training institutions to provide training requirements to qualify its employees and employees of other departments and to benefit from the competencies and training capabilities available in order to Raising the efficiency of the trainees within the various scientific and administrative specializations, as well as benefiting from these Courses to promote scientific and administrative development for associates in line with global development and progress. Hence the need to make maximum use of energies and requirements.